Development of Socio-Scientific Issues (SSI) Based Student Worksheets on Climate Change Material: Evaluation of Practicality and Effectiveness on Students' Scientific Attitudes - Rabiatul Hasanah; Ahmad Yadaeni; Dedi Riyan Rizaldi; Mahsur (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to develop a Socio-Scientific Issues (SSI)-based Student Worksheet (Lembar Kerja Peserta Didik, LKPD) on climate change material and evaluate its practicality and effectiveness on students' scientific attitudes. This research is development research with a 4D model that includes the define, design, develop, and disseminate stages. However, this article focuses on the development stage, especially the results of the practicality test and effectiveness test. The research subjects were grade X students of MAS Al-Chalil. The developed product has passed expert validity testing using Aiken's V index and obtained a value of more than 0.80, so it is declared valid and worthy of being tested. Practicality data were obtained through learning implementation sheets, teacher response questionnaires, and student response questionnaires, while effectiveness data were obtained through scientific attitude questionnaires given before and after learning. The results showed that the learning implementation obtained an average of 92%, teacher response of 91.25%, and student response of 89.08%, so the SSI-based Student Worksheet is included in the practical category. The results of the effectiveness test indicated that the average pretest score for students' scientific attitudes increased from 49.60 to 74.20 in the posttest, with an N-Gain value of 69.49%, which is categorized as moderate and interpreted as quite effective. The highest increase was in the sensitivity in investigating the environment indicator at 84.38%, while the lowest increase was in the curiosity indicator at 51.22%. Thus, the SSI-based LKPD on climate change material is practical and quite effective for improving students' scientific attitudes.